Improving Elementary School Students' Reading Comprehension Skills with Digital Flipbooks: Peningkatan Keterampilan Membaca Pemahaman Siswa Sekolah Dasar dengan Flipbook Digital - Sakinah, Al Wardatul Mustaghfirotus; Nuroh, Ermawati Zulikhatin (Indonesian Journal of Education Methods Development, 2025)
Background: Student reading comprehension skills are low, and digital learning media is rarely used in the classroom. Aims: This study aims to determine the implications and effects of using Flipbook media on the reading comprehension skills of fourth-grade students at SD Negeri Winong 1 in Indonesian language subjects. Methods: This study used a quantitative method with a one-group pretest-posttest design. Data were collected through tests and documentation and analyzed using eta squared, normality, and t-tests with SPSS 26. Results: The study found that flipbook media has a positive implication for students' reading comprehension skills and leads to increased student activity during the learning process. This is evidenced by an increase in student learning outcomes, with post-test scores showing an intensification compared to the low pre-test scores. Novelty: This study differs from previous research by specifically using digital flipbook media to measure its effect on reading comprehension skills in a high-grade Indonesian language class, a topic not explored in earlier studies. Implications: The use of digital flipbook media is effective in improving reading comprehension skills. Highlights : The study used a quantitative method with a one-group pretest-posttest design on 35 fourth-grade students at SD Negeri Winong 1. After the application of digital flipbook media, the average pre-test score of 40.0% increased significantly to an average post-test score of 82.2%. The use of flipbook media positively influences students' reading comprehension, increases their engagement, and supports their learning outcomes. Keywords : Digital Media, Flipbook, Reading Skills, Elementary School, Reading Comprehension